Occurrence and distribution of cowpea damping-off and stem rot and associated fungi in Benin - Adandonon, A.; Aveling, T.A.S.; Tamo, Manuele (Cambridge University Press, 2004)
Damping-off and stem rot of cowpea is an important soil-borne disease worldwide. Cowpea fields were randomly chosen in each agro-ecological zone in Benin and surveyed in 2001 and 2002 to determine the occurrence of the diseases throughout the country. Diseased plants, prevailing environmental conditions and cowpea grower cultural practices were recorded and causal agents associated with the disease identified. Results indicated that damping-off and stem rot were distributed throughout Benin. The disease incidence was higher in the South (0·074) and Centre zones (0·063) than in the other zones (<0·02) in the country. Among factors influencing the disease incidence, cultural practices such as sole crop and no-till systems appeared to be most important. Isolated fungi included Sclerotium rolfsii, Fusarium spp., Pythium ultimum, Rhizoctonia solani, Phoma sp., Rhizopus sp. and Trichoderma harzianum. None of the Fusarium, T. harzianum or Rhizopus sp. isolates were pathogenic in the greenhouse. Pythium ultimum, R. solani and Phoma sp. were infrequently isolated and few isolates caused the disease symptoms in the greenhouse. However, this is the first report of Phoma sp. causing damping-off and stem rot of cowpea in Benin. Sclerotium rolfsii was by far the most common species isolated from all the agro-ecological zones and all isolates were pathogenic on cowpea in the greenhouse. Sclerotium rolfsii was considered to be the main causal agent of cowpea damping-off and stem rot in the Republic of Benin due to its wide distribution, high incidence and predominance on plants with damping-off and stem rot symptoms.